Evaluation of TEGDMA leaching from four resin cements by HPLC - Altintas, Subutay Han; Usumez, Aslihan (European Journal of Dentistry, 2012)
Objectives: The aim of this study was to evaluate the elution of TEGDMA from dual cured resin cements, used for bonding of ceramic restoration by high performance liquid chromatography (HPLC).Methods: Forty freshly extracted caries and restoration free molar teeth used in this study. Standardized Class I preparations were prepared in all teeth. Ceramic inlays were cemented with one of the dual cured resin cements (Variolink II, Rely X ARC, Rely X Unicem and Resilute). After cementation, specimens were stored in 75% ethanol solution. HPLC was used to analyze the amounts of TEGDMA in different time intervals. Two-way ANOVA and Tukey HSD tests were used to evaluate the results (P<.05).Results: The amount of TEGDMA eluted from Resilute was the highest and the amount of TEGDMA eluted from Rely X Unicem was the lowest (P<.05). The total amount of monomers was the highest after 21 days (P<.05).Conclusions: The five soft drinks caused surface softening of enamel (erosion). In respect to the chemical variables tested, despite not statistically significant, the pH seems to have more influence on the erosive potential of these drinks. (Eur J Dent 2007;1:10-13)
Keywords: Residual Monomer; TEGDMA; resin cements; HPLC; ceramic; inlay; ethanol